Evaluation of the amyloid beta-GFP fusion protein as a model of amyloid beta peptides-mediated aggregation: A study of DNAJB6 chaperone - Hussein, Rasha M.; Hashem, Reem M.; Rashed, Laila A. (Frontiers in Molecular Neuroscience, 2015)
Alzheimer’s disease is a progressive neurodegenerative disease characterized by the accumulation and aggregation of extracellular amyloid β (Aβ) peptides and intracellular aggregation of hyper-phosphorylated tau protein. Recent evidence indicates that accumulation and aggregation of intracellular amyloid β peptides may also play a role in disease pathogenesis. This would suggest that intracellular Heat Shock Proteins (HSP) that maintain cellular protein homeostasis might be candidates for disease amelioration. We recently found that DNAJB6, a member of DNAJ family of heat shock proteins, effectively prevented the aggregation of short aggregation-prone peptides containing large poly glutamines (associated with CAG repeat diseases) both in vitro and in cells. Moreover, recent in vitro data showed that DNAJB6 can delay the aggregation of Aβ42 peptides. In this study, we investigated the ability of DNAJB6 to prevent the aggregation of extracellular and intracellular Aβ peptides using transfection of HEK293 cells with Aβ-GFP fusion construct and performing western blotting and immunofluorescence techniques. We found that DNAJB6 indeed suppresses Aβ-GFP aggregation, but not seeded aggregation initiated by extracellular Aβ peptides. Unexpectedly and unlike what we found for peptide-mediated aggregation, DNAJB6 required interaction with HSP70 to prevent the aggregation of the Aβ-GFP fusion protein and its J-domain was crucial for its anti-aggregation effect. In addition, other DNAJ proteins as well as HSPA1a overexpression also suppressed Aβ-GFP aggregation efficiently. Our findings suggest that Aβ aggregation differs from poly Q peptide induced aggregation in terms of chaperone handling and sheds doubt on the usage of Aβ-GFP fusion construct for studying Aβ peptide aggregation in cells.